Reprogramming with Small Molecules instead of Exogenous Transcription Factors - Tongxiang Lin; Shouhai Wu (Stem Cells International)
Induced pluripotent stem cells (iPSCs) could be employed in the creation of patient-specific stem cells, which could subsequently be used in various basic and clinical applications. However, current iPSC methodologies present significant hidden risks with respect to genetic mutations and abnormal expression which are a barrier in realizing the full potential of iPSCs. A chemical approach is thought to be a promising strategy for safety and efficiency of iPSC generation. Many small molecules have been identified that can be used in place of exogenous transcription factors and significantly improve iPSC reprogramming efficiency and quality. Recent studies have shown that the use of small molecules results in the generation of chemically induced pluripotent stem cells from mouse embryonic fibroblast cells. These studies might lead to new areas of stem cell research and medical applications, not only human iPSC by chemicals alone, but also safe generation of somatic stem cells for cell based clinical trials and other researches. In this paper, we have reviewed the recent advances in small molecule approaches for the generation of iPSCs.